x/a + y/b = a+b ; x/a^2 + y/b^2 = 2ab , b is not equal to 0
Answers
Answered by
0
Answer :
Given,
x/a + y/b = a + b ...(i)
x/a² + y/b² = 2ab ...(ii)
Now, multiplying (i) by 1/a and (ii) by 1, we get
x/a² + y/ab = (a + b)/a
x/a² + y/b² = 2ab
On subtraction, we get
y/ab - y/b² = (a + b)/a - 2ab
➽ (1/ab - 1/b²)y = (a + b - 2a²b)/a
➽ {(b - a)/ab²} y = (a + b - 2a²b)/a
➽ {(b - a)/b²} y = (a + b - 2a²b)
➽ y = b²(a + b - 2a²b)/(b - a)
Now, putting y = b²(a + b - 2a²b)/(b - a) in (i), we get
x/a + b²(a + b - 2a²b)/(b - a) = a + b
➽ x/a = (a + b) - b²(a + b - 2a²b)/(b - a)
➽ x/a = (ab + b² - a² - ab - ab² - b³ + 2a²b³)/(b - a)
➽ x/a = (b² - a² - ab² - b³ + 2a²b³)/(b - a)
➽ x = a(b² - a² - ab² - b³ + 2a²b³)/(b - a)
∴ The required solution be
x = a(b² - a² - ab² - b³ + 2a²b³)/(b - a)
y = b²(a + b - 2a²b)/(b - a)
#MarkAsBrainliest
Given,
x/a + y/b = a + b ...(i)
x/a² + y/b² = 2ab ...(ii)
Now, multiplying (i) by 1/a and (ii) by 1, we get
x/a² + y/ab = (a + b)/a
x/a² + y/b² = 2ab
On subtraction, we get
y/ab - y/b² = (a + b)/a - 2ab
➽ (1/ab - 1/b²)y = (a + b - 2a²b)/a
➽ {(b - a)/ab²} y = (a + b - 2a²b)/a
➽ {(b - a)/b²} y = (a + b - 2a²b)
➽ y = b²(a + b - 2a²b)/(b - a)
Now, putting y = b²(a + b - 2a²b)/(b - a) in (i), we get
x/a + b²(a + b - 2a²b)/(b - a) = a + b
➽ x/a = (a + b) - b²(a + b - 2a²b)/(b - a)
➽ x/a = (ab + b² - a² - ab - ab² - b³ + 2a²b³)/(b - a)
➽ x/a = (b² - a² - ab² - b³ + 2a²b³)/(b - a)
➽ x = a(b² - a² - ab² - b³ + 2a²b³)/(b - a)
∴ The required solution be
x = a(b² - a² - ab² - b³ + 2a²b³)/(b - a)
y = b²(a + b - 2a²b)/(b - a)
#MarkAsBrainliest
adityakul02p55okt:
BROTHER you have done mistake subtracting eq i and ii . in rhs of eq i , there is a+b/a and you write it a+b/ab and messed up the whole solution onwards. Pls correct this re-answer. thank you
Similar questions